In-depth characterization of light, medium and heavy oil asphaltenes as well as asphaltenes subfractions. (15th September 2022) - Salehzadeh, Marziyeh; Husein, Maen M.; Ghotbi, Cyrus; Dabir, Bahram; Taghikhani, Vahid
Graphical abstract: Highlights: Detailed analysis of asphaltenes originated from light, medium and heavy oils is provided. Asphaltenes are compared with least, intermediately and most soluble medium asphaltenes subfractions. Heavy oil asphaltenes and most soluble subfractions displayed least aromaticity and longest alkyl side chains. Precipitation/destabilization is majorly driven by π-π interactions and low steric hindrance. The effect of asphaltenes structures on their stability behavior is discussed. Abstract: Asphaltenes, and their related issues, have been the focus of many literature investigations. However, in-depth analysis of asphaltenes structure and its relation to asphaltenes stability has been considered by fewer studies. In this research, extensive analysis of the structure of asphaltenes extracted from light, medium, and heavy oils is provided, together with analysis of three subfractions of the medium oil asphaltene having the least, intermediate, and highest solubilities. To this end, elemental analysis, EDX, mass spectroscopy, FTIR, NMR, XRD, and SEM results were collected. Higher hydrogen content and hydrogen/carbon atomic ratio, lower aromatic nature and olefinic entities were observed in heavy oil asphaltenes as well as the most soluble subfraction. Moreover, the molecular structure of heavy oil asphaltenes and the most soluble subfraction displayed broader mass to charge ( m / z ) distribution range, longer alkyl side chains as well as higher number of stacked aromatic sheets within their nanoclusters. Asphaltenes hydrogens in α position followed similar trend as their heteroatom content, which was higher for the less soluble subfraction and medium oil asphaltenes. Generally, heavy oil asphaltenes possessed a molecular structure that was closer to the most soluble asphaltenes subfraction, whereas light oil asphaltenes possessed a molecular structure similar to the least soluble subfraction. Asphaltenes precipitation/destabilization was attributed to primarily higher attractive π-π interactions coupled with lower steric hindrance.